REPRESENTATIVENESS SATU SETASIUN HUJAN TERHADAP HUJAN RATA-RATA DAS - Ade Irawan (JURNAL PLANOLOGI DAN SIPIL (JPS), 2019)
Rain that happened in one catchment area is a very important value of that catchment area system. In arranging a water utilizing plan and flood controlling plan usually used cathment rainfall in all those catch area. In this study, to obtaining reduction coefficient (β) measurement, the regression analysys was done to coefficientt and constant from each parameters in reduction coefficient (β), likes catchment area width (A), number of rainfall gauges (N), and rainfall gauges elevation (E) using SPSS program. From the analysis, phase of calibration was used cathment rainfall and point rainfall bigger than 40 mm in 10 yaer, the average of error between reference- cathment rainfall with resulted cathment rainfall from multiplying with it’s reduction coefficient in the study (estimated- cathment rainfall) that is 15,0099 mm, or approximately 28,0718%. While, cathment rainfall result with its reduction coefficient was used for estimated design rainfall. For low return period (2 and 5 year) the smallest relative error was reached from this cathment rainfall product from reduction coefficient by the study. Meanwhile, for high return period (higher than 5 year), the smallest relative error was resulted from cathment rainfall Haspers’s reduction coefficient.